2014
DOI: 10.1093/icesjms/fsu132
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of the environmental impact of Norwegian Atlantic salmon farming

Abstract: Norwegian aquaculture has grown from its pioneering days in the 1970s to be a major industry. It is primarily based on culturing Atlantic salmon and rainbow trout and has the potential to influence the surrounding environment and wild populations. To evaluate these potential hazards, the Institute of Marine Research initiated a risk assessment of Norwegian salmon farming in 2011. This assessment has been repeated annually since. Here, we describe the background, methods and limitations of the risk assessment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
282
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(291 citation statements)
references
References 154 publications
3
282
1
1
Order By: Relevance
“…Similar findings have been reported from Norway (Grimnes et al 2000) and Scotland (Mackenzie et al 1998, Butler 2002. In a recent study, Taranger et al (2015) undertook a risk assessment of the effects of salmon lice on wild salmonid populations along the intensively farmed Norwegian coastline and found that sea trout from the majority of sampled sites had salmon lice infections, mainly resulting from salmon farming, which indicated moderate or high mortality risk of sea trout. In an extensive review of the impacts of the salmon louse on sea trout, Thorstad et al (2015) concluded that salmon farming increases the abundance of salmon lice in the marine habitat, and there is extensive published evidence that salmon lice in intensively farmed areas have negatively impacted wild sea trout populations by in creasing marine mortality, changes in migratory be haviour, reduction of marine growth and reduced population sizes.…”
Section: Discussionsupporting
confidence: 76%
“…Similar findings have been reported from Norway (Grimnes et al 2000) and Scotland (Mackenzie et al 1998, Butler 2002. In a recent study, Taranger et al (2015) undertook a risk assessment of the effects of salmon lice on wild salmonid populations along the intensively farmed Norwegian coastline and found that sea trout from the majority of sampled sites had salmon lice infections, mainly resulting from salmon farming, which indicated moderate or high mortality risk of sea trout. In an extensive review of the impacts of the salmon louse on sea trout, Thorstad et al (2015) concluded that salmon farming increases the abundance of salmon lice in the marine habitat, and there is extensive published evidence that salmon lice in intensively farmed areas have negatively impacted wild sea trout populations by in creasing marine mortality, changes in migratory be haviour, reduction of marine growth and reduced population sizes.…”
Section: Discussionsupporting
confidence: 76%
“…The high level of genetic differentiation between these fish and native populations (Table 3) is likely to increase the level of genetic change resulting from introgression (Glover et al 2013). Taranger et al (2015) concludes that the risk of genetic introgression is considered high, with a frequency of escapees >10% and low risk < 4%. The results of the present study suggest that in Cyprus the risk of introgression is in general moderate, but at certain locations there is a very high risk of interbreeding due to the high number of escapees present.…”
Section: Discussionmentioning
confidence: 99%
“…Global aquaculture is the fastest growing food-producing sector, with nearly half of the world's seafood supply now sourced from aquaculture (FAO 2012). A main challenge facing this industry is sustaining a continued increase in fish production while minimizing the impact on the environment (Sugiura et al 2006, 1994, Phillips et al 1991) and the rapid expansion of caged fish culture has raised a general concern about the release of solid and dissolved waste products to the environment (Troell & Norberg 1998, Perez et al 2002, Cheshuk et al 2003, Whitmarsh et al 2006, Valdemarsen et al 2012, Taranger et al 2015. Conspicuous environmental ef fects can stem from the increased organic matter loading on the seafloor, and consequential changes in benthic habitat and communities (Strain & Hargrave 2005, Kutti et al 2007).…”
Section: Introductionmentioning
confidence: 99%